2020
DOI: 10.1101/2020.01.27.915470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-read sequencing reveals widespread intragenic structural variants in a recent allopolyploid crop plant

Abstract: Phone: +49 641 9937420 20 21 22 highly-duplicated nature of plant genomes, which makes them difficult to assess using high-31throughput genome screening methods. Here we describe how long-read sequencing 32 technologies can overcome this problem, revealing a surprisingly high level of widespread, 33 small to mid-scale SV in a major allopolyploid crop species, Brassica napus. We found that 34 up to 10% of all genes were affected by small to mid-scale SV events. Nearly half of these 35 SV events ranged between 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Quantitative disease resistance has previously been associated with presence/absence genetic variation (Gabur et al ., 2018, 2020) and homoeologous recombination (Zhao et al ., 2006) in Brassica napus . In addition, recent whole‐genome analyses using long‐read sequence data (Song et al ., 2020) has revealed genetic variability affecting plant disease resistance to be enriched in genomic regions impacted by structural variation, including that due to homoeologous recombination in allopolyploid species (Chawla et al ., 2021; Hurgobin et al ., 2018; Samans et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative disease resistance has previously been associated with presence/absence genetic variation (Gabur et al ., 2018, 2020) and homoeologous recombination (Zhao et al ., 2006) in Brassica napus . In addition, recent whole‐genome analyses using long‐read sequence data (Song et al ., 2020) has revealed genetic variability affecting plant disease resistance to be enriched in genomic regions impacted by structural variation, including that due to homoeologous recombination in allopolyploid species (Chawla et al ., 2021; Hurgobin et al ., 2018; Samans et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] and benchmarked [26], typically performing better than methods using short reads. These approaches have recently been applied to provide genome-wide assessments of SVs in crops such as tomato [12], rice (Oryza sativa) [27] and rapeseed [28].…”
Section: Introductionmentioning
confidence: 99%
“…While the cost of whole‐genome sequencing in wheat is not yet feasible for individual breeding programs, long‐read sequencing and greater fold coverage (i.e., 10) has become increasingly affordable. Longer sequencing reads can detect even small‐ (30–10,000 bp) to mid‐scale (10,000–30,000 bp) structural variants, which impact trait diversity and are shown to be widespread in polyploid species (Chawla et al., 2021; Gabur et al., 2019; Mahmoud et al., 2019). For example, a recent study of Brassica napus L. found that up to 10% of all genes were affected by small‐ to mid‐scale structural variants including flowering‐time pathway genes, which can influence agronomic traits (Chawla et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Longer sequencing reads can detect even small‐ (30–10,000 bp) to mid‐scale (10,000–30,000 bp) structural variants, which impact trait diversity and are shown to be widespread in polyploid species (Chawla et al., 2021; Gabur et al., 2019; Mahmoud et al., 2019). For example, a recent study of Brassica napus L. found that up to 10% of all genes were affected by small‐ to mid‐scale structural variants including flowering‐time pathway genes, which can influence agronomic traits (Chawla et al., 2021). Obtaining long‐read sequencing (small‐ to mid‐scale structural variants) or 10‐fold coverage (large‐scale structural variants) of parental lines for a mapping population could become a prerequisite first‐step in positional cloning population development. Use the transcriptome to identify candidate genes .…”
Section: Discussionmentioning
confidence: 99%